DEFINITION ty3_predicative()
TYPE =
∀g:G
.∀c:C
.∀v:T.∀t:T.∀u:T.(ty3 g c (THead (Bind Abst) v t) u)→(pc3 c u v)→∀P:Prop.P
BODY =
assume g: G
assume c: C
assume v: T
assume t: T
assume u: T
suppose H: ty3 g c (THead (Bind Abst) v t) u
suppose H0: pc3 c u v
assume P: Prop
(H1) consider H
by (ty3_gen_bind . . . . . . H1)
we proved
ex3_2
T
T
λt2:T.λ:T.pc3 c (THead (Bind Abst) v t2) u
λ:T.λt:T.ty3 g c v t
λt2:T.λ:T.ty3 g (CHead c (Bind Abst) v) t t2
we proceed by induction on the previous result to prove P
case ex3_2_intro : x0:T x1:T :pc3 c (THead (Bind Abst) v x0) u H3:ty3 g c v x1 :ty3 g (CHead c (Bind Abst) v) t x0 ⇒
the thesis becomes P
(H_y)
by (ty3_conv . . . . H3 . . H H0)
ty3 g c (THead (Bind Abst) v t) v
end of H_y
(H_x)
by (ty3_arity . . . . H_y)
ex2
A
λa1:A.arity g c (THead (Bind Abst) v t) a1
λa1:A.arity g c v (asucc g a1)
end of H_x
(H5) consider H_x
we proceed by induction on H5 to prove P
case ex_intro2 : x:A H6:arity g c (THead (Bind Abst) v t) x H7:arity g c v (asucc g x) ⇒
the thesis becomes P
(H8)
by (arity_gen_abst . . . . . H6)
ex3_2
A
A
λa1:A.λa2:A.eq A x (AHead a1 a2)
λa1:A.λ:A.arity g c v (asucc g a1)
λ:A.λa2:A.arity g (CHead c (Bind Abst) v) t a2
end of H8
we proceed by induction on H8 to prove P
case ex3_2_intro : x2:A x3:A H9:eq A x (AHead x2 x3) H10:arity g c v (asucc g x2) :arity g (CHead c (Bind Abst) v) t x3 ⇒
the thesis becomes P
(H12)
we proceed by induction on H9 to prove arity g c v (asucc g (AHead x2 x3))
case refl_equal : ⇒
the thesis becomes the hypothesis H7
arity g c v (asucc g (AHead x2 x3))
end of H12
by (arity_mono . . . . H12 . H10)
we proved leq g (asucc g (AHead x2 x3)) (asucc g x2)
that is equivalent to leq g (AHead x2 (asucc g x3)) (asucc g x2)
by (leq_ahead_asucc_false . . . previous .)
P
P
P
we proved P
we proved
∀g:G
.∀c:C
.∀v:T.∀t:T.∀u:T.(ty3 g c (THead (Bind Abst) v t) u)→(pc3 c u v)→∀P:Prop.P